Indirect costs of adult pneumococcal disease and the productivity-based rate of return to the 13-valent pneumococcal conjugate vaccine for adults in Turkey - J. P. Sevilla; Andrew Stawasz; Daria Burnes; Anubhav Agarwal; Basak Hacibedel; Kerem Helvacioglu; Reiko Sato; David E. Bloom (Taylor & Francis Group, 2020)
Productivity benefits of health technologies are ignored in typical economic evaluations from a health payer's perspective, risking undervaluation. We conduct a productivity-based cost-benefit analysis from a societal perspective and estimate indirect costs of adult pneumococcal disease, vaccination benefits from the adult 13-valent pneumococcal conjugate vaccine (PCV13 Adult), and rates of return to PCV13 Adult for a range of hypothetical vaccination costs. Our context is Turkey's funding PCV13 for the elderly and for non-elderly adults with select comorbidities within the Ministry of Health's National Immunization Program. We use a Markov model with one-year cycles. Indirect costs from death or disability equal the expected present discounted value of lifetime losses in the infected individual's paid and unpaid work and in caregivers' paid work. Vaccination benefits comprise averted indirect costs. Rates of return equal vaccination benefits divided by vaccination costs, minus one. Input parameters are from public data sources. We model comorbidities' effects by scalar multiplication of the parameters of the general population. Indirect costs per treatment episode of inpatient community-acquired pneumonia (CAP), bacteremia, and meningitis - but not for outpatient CAP - approach or exceed Turkish per capita gross domestic product. Vaccination benefits equal $207.02 per vaccination in 2017 US dollars. The rate of return is positive for all hypothetical costs below this. Results are sensitive to herd effects from pediatric vaccination and vaccine efficacy rates. For a wide range of hypothetical vaccination costs, the rate of return compares favorably with those of other global development interventions with well-established strong investment cases.